Pengaruh Nilai Hydrophile-Liphophile Balance (HLB) dan Jenis Ekstrak terhadap Karakteristik Krim Kunyit-Lidah Buaya (Curcuma domestica val.-Aloe Vera) - I Gusti Ayu Sri Krsna Devi; Sri Mulyani; Lutfi Suhendra (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2019)
This study aimed to determine the effect of value Hydrophile-Liphophile Balance (HLB) and type of extract on the characteristics of turmeric-aloe vera cream (Curcuma domestica Val. – Aloe Vera) also determine the HLB and the right type of extract to produce the best characteristics of turmeric-aloe vera cream (Curcuma domestica Val. – Aloe Vera). This study used a factorial randomized block design with two factor. The first factor was the HLB which consist of three levels, namely HLB 9, 10 and 11. The second factor was an extract consisting of two levels, namely the addition of turmeric and aloe vera extract. The result of the study showed that HLB has an effect on the spread power. The extract has an effect on the degree of acidity and total phenol. The treatment of HLB and the addition of the extract did not affect homogeneity, separation ratio, viscocity and adhesion time. All creams fulfill the characteristics of SNI. Aloe vera and turmeric extract cream with HLB 10 were the best formulated cream at the 6th week storage of the following characteristics: homogeneus, separation ratio =1, spread power 4.8-5.2 cm, viscocity 15733–16667 cp, adhesion time 14.43–17.31 second, pH 4.87-5.00 and total phenol 1.08–1.36 mg GAE/g.